Wajah Multukuralisme Islam yang Tersingkirkan (Analisis Struktural Fungsional Kurikulum Mata Pelajaran Sosiologi Pada Madrasah) - Miftahusyai`an, Mohammad (Cendekia: Jurnal Kependidikan dan Kemasyarakatan, 2017)
This study examined behavioral approach in dealing with students’ indiscipline behavior at SMP Diponegoro Depok Sleman Yogyakarta whose family background of divorce. Qualitative descriptive methodwas applied to reveal the above phenomenon and the data were collected by observation and in-depth interview. It revealed that there were three main steps in applying this behavior approach. Firstly, assessment was essentially conducted in advance to investigate the underlying factors which cause indiscipline to happen. The second step was a goal setting; discussing with students about the consequences that might be faced when they engage in undisciplined behavior. At this stage, the researcher along with the students had succeeded in devising a plan to solve the problem. The last stage was that carrying out the research to assess students followed by counseling contract, relaxation, modeling, reward and punishment, encouragement, time-out, home assignment and ending with the evaluation phase. The results found that behavioral technique was one of effective approaches in guidance and counseling to handle maladaptive on adaptive behavior, and this approach was very appropriate to handle undisciplined students in school. Ø§Ù„Ù‡Ø¯Ù Ø§Ù„Ø±Ø¦ÙŠØ³ÙŠ Ù…Ù† ØªØ¹Ù„ÙŠÙ… ØªØ¹Ø¯Ø¯ÙŠØ© Ø§Ù„Ø«Ù‚Ø§ÙØ§Øª Ø¹Ù† Ø·Ø±ÙŠÙ‚ ØªØ¹Ù„ÙŠÙ… Ù…Ø§Ø¯Ø© Ø¹Ù„Ù… Ø§Ù„Ø§Ø¬ØªÙ…Ø§Ø¹ ÙÙŠ Ø§Ù„Ù…Ø¯Ø§Ø±Ø³ Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ù‡Ùˆ Ø¥Ø¹Ø¯Ø§Ø¯ Ø§Ù„Ø·Ù„Ø§Ø¨ Ù„ÙŠØ¹ÙŠØ´ÙˆØ§ Ø¨ÙŠÙ† Ø§Ù„Ù…Ø¬ØªÙ…Ø¹ Ù…ØªØ±Ø§ØÙ…ÙŠÙ† ÙÙŠÙ…Ø§ Ø¨ÙŠÙ†Ù‡Ù… Ø·Ø¨Ù‚Ø§ Ù„Ù„Ù‚ÙŠÙ… ÙÙŠ Ø¨Ù†ØªØ´Ø§Ø³ÙŠÙ„Ø§. ÙˆØ¥Ù† ØØ§Ù„Ø© Ù…Ø¬ØªÙ…Ø¹Ù‡Ù… Ø¬ÙŠØ¯Ø© Ù„Ø§ÙŠÙØ±Ù‘Ù‚ÙˆÙ† ÙÙŠÙ…Ø§ ÙŠØ¹ØªÙ‚Ø¯ÙˆÙ† Ø¨Ù‡ Ù…Ù† Ø§Ù„Ø£Ø¯ÙŠØ§Ù†ØŒ ÙˆÙ‡Ø°Ø§ Ø§Ù„Ø£Ù…Ø± Ø¨Ø¶Ø§Ø¹Ø© Ù„Ø§Ø¨Ø¯ Ù…Ù† Ø§Ø«Ø¨Ø§ØªÙ‡Ø§ ÙÙŠ Ù†ÙÙˆØ³Ù‡Ù…. ÙˆØ§Ù„ÙˆØ§Ù‚Ø¹ Ø¥Ù† ØªØ¹Ù„ÙŠÙ… Ø¹Ù„Ù… Ø§Ù„Ø§Ø¬ØªÙ…Ø§Ø¹ ÙÙŠ Ø§Ù„Ù…Ø¯Ø§Ø±Ø³ Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© ÙŠØ¶ÙŠØ¹ ÙÙŠÙ‡ Ø±ÙˆØÙ‡. ÙˆØ£ØµØ¨Ø ØªØ¹Ù„ÙŠÙ… Ù‡Ø°Ù‡ Ø§Ù„Ù…Ø§Ø¯Ø© Ø¹ÙØ¨Ø¦Ø§ Ø¬Ø¹Ù„ Ø§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„Ø¯Ø±Ø§Ø³ÙŠÙ‘ Ø³Ù…ÙŠÙ†Ø§ ÙˆØ£ØµØ¨ØØª Ø§Ù„Ù…Ø§Ø¯Ø© Ù…Ø¬Ù…Ù„Ø© ÙÙŠ Ø³Ø·ÙˆØ± Ù„ÙƒÙ†Ù‡Ø§ Ø£ØµØ¨ØØª Ù…Ø§Ø¯Ø© Ù‚Ø¯ÙŠÙ…Ø© ØÙŠÙ† Ø¹Ù„Ù…Ù‡Ø§ Ø§Ù„Ù…Ø¯Ø±Ø³ Ù†ØÙˆ Ø§Ù„Ø·Ù„Ø§Ø¨. Ù„Ø°Ø§ ÙØ¥Ù†Ù‡ Ù…Ù‡Ù… Ù„Ù„Ù…Ø¯Ø±Ø³ Ø¬Ø¹Ù„ Ø§Ù„Ù…ÙÙ‡ÙˆÙ… ÙÙŠ “ ÙƒÙŠÙ Ø¨Ù†Ø§Ø¡ Ø§Ù„ØªÙˆØ§ØµÙ„Ø§Øª Ø§Ù„Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠØ© “ Ø§Ù„Ù…Ø³Ø§Ø¹Ø¯Ø© Ù„Ù‡ ÙÙŠ Ø£Ø¯Ø§Ø¡ Ø¹Ù…Ù„Ù‡. ÙˆÙ…Ù…Ø§ ÙŠÙ†Ø¨ØºÙŠ ”“ Ø¹Ù„Ù‰ Ø§Ù„Ù…Ø¯Ø±Ø³ ”“ Ø§Ù„Ù‚ÙŠØ§Ù… Ø¨Ù‡ : 1( Ø¨Ø¯Ø£ Ø§Ù„Ù…Ø¯Ø±Ø³ ÙŠØ¨ØØ« Ø¹Ù† Ø´ÙƒÙ„ Ø§Ù„Ø¹Ù„Ø§Ù‚Ø© Ø§Ù„Ù‚ÙˆÙŠØ© ÙˆØ§Ù„Ù‚Ø±ÙŠØ¨Ø© Ø¨Ù…Ù† ÙÙŠ Ø¨ÙŠØ¦Ø© Ø§Ù„Ù…Ø¯Ø±Ø³Ø©. Ù‡Ø°Ù‡ Ø§Ù„Ø¹Ù„Ø§Ù‚Ø© ÙŠÙ…ÙƒÙ† Ø£Ù† ØªÙƒÙˆÙ† ÙÙŠ Ø´Ø¨ÙƒØ§Øª Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠØ© Ù…ØªØ¬Ø§Ù†Ø³Ø©ØŒ 2( ØØ§ÙˆÙ„ Ø§Ù„Ù…Ø¯Ø±Ø³ Ø§Ù„ØØµÙˆÙ„ Ø¹Ù„Ù‰ Ø´ÙƒÙ„ Ø§Ù„ØªÙˆØ§ØµÙ„ Ø§Ù„Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠ Ø§Ù„Ù…ØªÙØªÙ‘Ø ÙˆØ§Ù„Ù…ÙˆØ³Ù‘Ø¹ ÙˆØ¹Ù„Ù‰ Ø§Ù„Ø¬Ù…ÙŠØ¹. Ù‡Ø°Ù‡ Ø§Ù„ØªÙˆØ§ØµÙ„Ø§Øª ÙŠÙ…ÙƒÙ† Ø£Ù† ØªÙƒÙˆÙ† ÙÙŠ Ø´Ø¨ÙƒØ§Øª Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠØ© Ù…ØªÙ†ÙˆÙ‘Ø¹Ø©